1993
DOI: 10.1002/1097-0142(19930501)71:9<2817::aid-cncr2820710922>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule-1 (ICAM-1) staining of reactive and neoplastic follicles. ICAM-1 expression of neoplastic follicle differs from that of reactive germinal center and is independent of follicular dendritic cells

Abstract: Background. Intercellular adhesion molecule‐1 (ICAM‐1) is expressed on follicular dendritic cells (FDC), and the ICAM‐1/LFA‐1 pathway is essential for affinity selection of activated B‐cells in germinal centers (GC). The expression of ICAM‐1 has been studied by immunostaining methods in GC, but not in neoplastic follicles (NF). Methods. The authors studied the expression of ICAM‐1 by the avidin‐biotin‐peroxidase complex (ABC) method with frozen sections in GC of reactive nodes (n = 22) and NF of follicular lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…In our search to refine the immunophenotype of GCDCs allowing their identification in situ and their distinction from extrafollicular DCs, we found that CD54/ICAM-1 expression seemed to be a specific marker for GCDCs and was not detected on extrafollicular DCs. A few studies were devoted to the in situ immunolocalization of ICAM-1 in GC (Dustin et al 1986;Koopman et al 1991;Ree et al 1993). As with these authors, we found that GCs stained strongly and uniformly for ICAM-1.…”
Section: Discussionsupporting
confidence: 86%
“…In our search to refine the immunophenotype of GCDCs allowing their identification in situ and their distinction from extrafollicular DCs, we found that CD54/ICAM-1 expression seemed to be a specific marker for GCDCs and was not detected on extrafollicular DCs. A few studies were devoted to the in situ immunolocalization of ICAM-1 in GC (Dustin et al 1986;Koopman et al 1991;Ree et al 1993). As with these authors, we found that GCs stained strongly and uniformly for ICAM-1.…”
Section: Discussionsupporting
confidence: 86%